CsPbBr3 Nanocrystal Films: Deviations from Bulk Vibrational and Optoelectronic Properties. (5th March 2020) - Motti, Silvia G.; Krieg, Franziska; Ramadan, Alexandra J.; Patel, Jay B.; Snaith, Henry J.; Kovalenko, Maksym V.; Johnston, Michael B.; Herz, Laura M.
Abstract: Metal‐halide perovskites (MHP) are highly promising semiconductors for light‐emitting and photovoltaic applications. The colloidal synthesis of nanocrystals (NCs) is an effective approach for obtaining nearly defect‐free MHP that can be processed into inks for low‐cost, high‐performance device fabrication. However, disentangling the effects of surface ligands, morphology, and boundaries on charge‐carrier transport in thin films fabricated with these high‐quality NCs is inherently difficult. To overcome this fundamental challenge, terahertz (THz) spectroscopy is employed to optically probe the photoconductivity of CsPbBr3 NC films. The vibrational and optoelectronic properties of the NCs are compared with those of the corresponding bulk polycrystalline perovskite and significant deviations are found. Charge‐carrier mobilities and recombination rates are demonstrated to vary significantly with the NC size. Such dependences derive from the localized nature of charge carriers within NCs, with local mobilities dominating over interparticle transport. It is further shown that the colloidally synthesized NCs have distinct vibrational properties with respect to the bulk perovskite, exhibiting blue‐shifted optical phonon modes with enhanced THz absorption strength that also manifest as strong modulations in the THz photoconductivity spectra. Such fundamental insights into NC versus bulk properties will guide the optimization of nanocrystalline perovskite thin films for optoelectronic applications. Abstract : The optoelectronic properties of CsPbBr3 nanocrystal films are investigated in comparison to those of a bulk polycrystalline film. The terahertz photoconductivity shows localization of charge carriers in nanocrystals even after partial sintering. The nanocrystals show expansion of the lattice, blue‐shifted phonon spectra, and enhanced coupling of phonon modes to the terahertz probe with respect to the bulk.